2007
DOI: 10.1111/j.1365-2893.2007.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability and efficacy of peginterferon alpha‐2a and ribavirin in chronic hepatitis C in clinical practice: The German Open Safety Trial

Abstract: OnlineOpen: This article is available free online at www.blackwell-synergy.com SUMMARY. The combination treatment of peginterferon alpha-2a (PEG-IFN alpha-2a; Pegasys Ò ) plus ribavirin (RBV) is recommended as a standard care for HCV infections. Side effects and aspects of efficacy and safety have to be balanced. This study evaluates clinical practice data on safety and efficacy of HCV treatment with PEG-IFN in combination with RBV over 24 and 48 weeks. This study was a phase III, multi-centre, open-label stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
24
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 22 publications
8
24
0
2
Order By: Relevance
“…In another randomized controlled trial [22] comparing the efficacy and safety of Peg-IFN-a-2a 135 lg/ week, Peg-IFN-a-2a 180 lg/week, and IFN-a-2a in patients with CHC, the overall safety profiles were similar for the three different treatments. According to our analysis, we agree with these previous reports [22,39] that the dosage and duration of IFN therapy seem to have no significant effect on the safety profile.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In another randomized controlled trial [22] comparing the efficacy and safety of Peg-IFN-a-2a 135 lg/ week, Peg-IFN-a-2a 180 lg/week, and IFN-a-2a in patients with CHC, the overall safety profiles were similar for the three different treatments. According to our analysis, we agree with these previous reports [22,39] that the dosage and duration of IFN therapy seem to have no significant effect on the safety profile.…”
Section: Discussionsupporting
confidence: 82%
“…In a study for evaluating clinical practice data on safety and efficacy of HCV treatment with Peg-IFN in combination with ribavirin over 24 and 48 weeks, the safety profile was similar and showed the highest incidence of AEs in the first 12 weeks of treatment [39]. In another randomized controlled trial [22] comparing the efficacy and safety of Peg-IFN-a-2a 135 lg/ week, Peg-IFN-a-2a 180 lg/week, and IFN-a-2a in patients with CHC, the overall safety profiles were similar for the three different treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Our results regarding genotypes as the strong predictors of SVR correspond to the data of the majority of other investigators obtained in RCT and in "real life" studies [10,24,25,28,31,32,33,40,42,46,[48][49][50].…”
Section: Discussionsupporting
confidence: 71%
“…Danish nationwide cohort study [38], presented the data obtained in a routine clinical practice and found them comparable to those observed in controlled clinical trials: overall 57.9 % of patients achieved SVR: it was 46.5 % in patients with genotype 1/4 infection and 77.3 % in those with genotype 2/3 infection. Some other authors [39][40][41][42][43][44][45] and community based studies in Germany, Canada, France and Australia [46][47][48][49][50][51] reported SVR data comparable with those in RCT too. Conversely, results of other investigators were lower [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation